What arguments and from whom are most influential in shaping public health policy: thematic content analysis of responses to a public consultation on the regulation of television food advertising to children in the UK - Martin White; J Adams; Ahmed Razavi (BMJ Open)
Objectives We explore one aspect of the decision making process—public consultation on policy proposals by a national regulatory body—aiming to understand how public health policy development is influenced by different stakeholders.Design We used thematic content analysis to explore responses to a national consultation on the regulation of television advertising of foods high in fat, salt and sugar aimed at children.Setting UK.Results 139 responses from key stakeholder groups were analysed to determine how they influenced the regulator’s initial proposals for advertising restrictions. The regulator’s priorities were questioned throughout the consultation process by public health stakeholders. The eventual restrictions implemented were less strict in many ways than those originally proposed. These changes appeared to be influenced most by commercial, rather than public health, stakeholders.Conclusions Public health policy making appears to be considered as a balance between commercial and public health interests. Tactics such as the questioning and reframing of scientific evidence may be used. In this example, exploring the development of policy regulating television food advertising to children, commercial considerations appear to have led to a watering down of initial regulatory proposals, with proposed packages not including the measures public health advocates considered to be the most effective. This seems likely to have compromised the ultimate public health effectiveness of the regulations eventually implemented.